Pendidikan Kesehatan Reproduksi Remaja dan Sosialisasi Produk Hukum Sebagai Usaha Promotif dan Preventif Pelecahan Seksual di Pondok Pesantren Sofa Marwa Pakusari Jember - Fitrianingtyas, Rizki; Anggitasari, Wima; Mutiah, Dewi (Proceedings of Annual Conference on Community Engagement, 2022)
Adolescent are teenagers, youth and a young person was 10-19 years old (WHO), 15-24 years old (UNFPA), 10-24 years old (WHO &UNFPA). The age of a teenager spent in educational environment for example schools, in boarding school and college. Compared to another age, a teenage thing more complex as it enters strorm problem and the stress of puberty. It is also quite high sexual violence in adolescents .The sexual violence and people aged 13-18 year some 200 / year reported cases .It includes a number of violence in a hut boarding .Methods used is education , socialization and discussions about sex education and law of sexual harassment by the presentation in indonesia , integration and discussions with 4 times face to face .As a result almost 50 % santriwati experienced sexual violence in the form of cat calling , palpable area sensitive by the 25% and the nearest  santriwan ever perpetrated cat calling. From the results of the questionnaire, knowledge was obtained after giving education, there was an increase in knowledge of less than 0 %, enough for 7% and good for 93%. Increased knowledge of Anatomy Physiology of reproductive organs, characteristics of puberty, maintaining genital organs and legal products regarding sexual harassment. This is useful in reducing the number of sexual violence against adolescents and it is hoped that other Islamic Boarding Schools will do this.